1971
DOI: 10.1111/j.1348-0421.1971.tb00613.x
|View full text |Cite
|
Sign up to set email alerts
|

The Germination Requirements of Spores of Clostridium botulinum Type E

Abstract: The requirements for, and conditions influencing, the germination of spores of Clostridium botulinum type E were studied in chemically defined media. Spores of this organism germinated rapidly and completely in various combinations of L-alanine and one of such carbon sources as sugars, lactate, and ribosides in the presence of bicarbonate. The most effective compounds tested were glucose, L-and D-lactate, and inosine. The formation of lactic acid was found to occur during germination of spores in a combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…Spores of C. botulinum Group II also respond to a variety of amino acids ( Table 1 ) (Ando and Iida, 1970; Ando, 1971; Plowman and Peck, 2002). In contrast to C. botulinum Group I, L -lactate is considered essential for amino acid induced germination in C. botulinum Group II (Plowman and Peck, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spores of C. botulinum Group II also respond to a variety of amino acids ( Table 1 ) (Ando and Iida, 1970; Ando, 1971; Plowman and Peck, 2002). In contrast to C. botulinum Group I, L -lactate is considered essential for amino acid induced germination in C. botulinum Group II (Plowman and Peck, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to C. botulinum Group I, L -lactate is considered essential for amino acid induced germination in C. botulinum Group II (Plowman and Peck, 2002). The germination responses of C. botulinum Group II is dependent on strain, pH, temperature, and buffer (Ando and Iida, 1970; Ando, 1971; Plowman and Peck, 2002; Peck, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…L ‐alanine, L ‐cysteine, L ‐serine, L ‐threonine) induced germination of spores of non‐proteolytic Cl. botulinum type E (strain Iwanai) at pH 9·0 in the presence of NaHCO 3 (Ando 1971). At neutral pH, a situation more relevant to food, germination by a single amino acid was moderate, but multi‐component mixtures triggered extensive germination (Ando and Iida 1970).…”
Section: Discussionmentioning
confidence: 99%
“…At neutral pH, a situation more relevant to food, germination by a single amino acid was moderate, but multi‐component mixtures triggered extensive germination (Ando and Iida 1970). Subsequent work confirmed that while L ‐alanine (25 mmol l −1 )/NaHCO 3 (60 mmol l −1 ) in phosphate buffer (40 mmol l −1 , pH 6·8) had no effect, further addition to the mixture of glucose, galactose, maltose, glucose‐6‐phosphate, fructose‐1,6‐diphosphate, L ‐lactate, D ‐lactate, DL ‐lactate, guanosine or inosine at 2–20 mmol l −1 induced germination of spores of strain Iwanai (Ando 1971). A number of alpha‐hydroxy acids were also effective (Ando 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation